2019
DOI: 10.1039/c9tc00506d
|View full text |Cite
|
Sign up to set email alerts
|

Thermally self-managing YAG:Ce–Al2O3color converters enabling high-brightness laser-driven solid state lighting in a transmissive configuration

Abstract: High-brightness laser-driven white light can be achieved by just controlling the Al2O3content and/or the thickness of YAG:Ce–Al2O3composite ceramics under blue laser excitation in a transmissive configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…Besides, although the SCs, TCs, and CCPs all show good thermal conductivity, most of the blue laser cannot be converted or trapped due to the lack of light scattering centers in SCs and TCs, leading to a low luminous efficiency. 15,16 Recently, Yao et al reported an optimized YAG: Ce TC with nano-defects, which increases the Rayleigh-Mie scattering of the incident blue LD light leading to a high luminous efficiency of 223 lm•W −1 for laser-driven lighting. 3 Nevertheless, the performances of optimized YAG: Ce TC driven under high-power laser are not investigated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, although the SCs, TCs, and CCPs all show good thermal conductivity, most of the blue laser cannot be converted or trapped due to the lack of light scattering centers in SCs and TCs, leading to a low luminous efficiency. 15,16 Recently, Yao et al reported an optimized YAG: Ce TC with nano-defects, which increases the Rayleigh-Mie scattering of the incident blue LD light leading to a high luminous efficiency of 223 lm•W −1 for laser-driven lighting. 3 Nevertheless, the performances of optimized YAG: Ce TC driven under high-power laser are not investigated.…”
mentioning
confidence: 99%
“…So far, the reflective configuration is usually adopted owing to easy heat dissipation by attaching the phosphor converters to heat sink. 16 (Aladdin, 50 nm, 99.99%) were used as the raw materials. A reverse strike co-precipitation method using nitrates and ammonia (Aladdin, 25-28%, GR) was adopted to prepare the Lu 2 O 3 nano-powders (around 100 nm).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the phosphor materials must withstand long‐term high flux density laser irradiations and dissipate the generated heat within the small laser spot. Based on this guideline, a variety of robust phosphor ceramics and luminescent single crystals, especially Y 3 Al 5 O 12 (YAG)‐based materials, have been studied . However, the high refractive index of crystalline materials causes a quite small critical angel and thus strong total internal reflection (TIR), seriously deteriorating the light extraction efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, light scattering centers must be introduced. Recently, the YAG:Ce‐Al 2 O 3 composite ceramic has been proposed for use in laser lighting because of its: i) high thermal conductivity and ii) high luminous efficacy caused by the scattering of secondary Al 2 O 3 grains . However, the refractive index difference between YAG (≈1.82) and Al 2 O 3 (≈1.76) is quite small, even smaller than that between silicone (≈1.50) and YAG:Ce phosphor (≈1.82) which are widely used in white LEDs.…”
Section: Introductionmentioning
confidence: 99%